Calling invisible women : a novel - Ray, Jeanne (Crown Publishers, 2012)
Feeling unattractive and unappreciated as she enters her fifties, wife and mother Clover wakes up one morning and discovers that she has actually become invisible, a condition that goes unnoticed by her family.